Simultaneous Impact of Hollow Droplet and Continuous Dense Droplet on Liquid Film - Li, Dashu; Liang, Gangtao; Hua, Dan (Frontiers in Energy Research, 2022)
Simultaneous impact of a hollow droplet and a continuous dense droplet on a liquid film is investigated using the coupled level set and volume of fluid (CLSVOF) method. Analyses includes fluid dynamics and heat transfer characteristics in impact. Results show that the interfacial phenomena after impact incorporate spreading, central jet between droplets, edge liquid sheet and counter jet inside hollow droplet. Pressure gradient is the major cause for the above phenomena. The significant parameter of impact velocity is closely related to the dynamics and heat transfer for droplets impacting on liquid film. Droplets with higher impact velocity exhibit a greater spreading factor, central jet height, edge jet height and counter jet height. Besides, wall heat flux increases more notably for droplets with higher impact velocity. Compared to the continuous droplet, the hollow droplet shows a smaller spreading factor and edge jet height, a higher wall heat flux but a narrow thermally affected region. This study provides a fundamental understanding for the application of high pressure spray combustion.